ω-3 Ethyl ester results in better cognitive function at 12 and 30 months than control in cognitively healthy subjects with coronary artery disease: a secondary analysis of a randomized clinical trial - Malik, Abdulaziz; Ramadan, Amira; Vemuri, Bhavya; Siddiq, Wardah; Amangurbanova, Maral; Ali, Aamir; Welty, Francine K (The American journal of clinical nutrition, 2021)
Omega-3 (n–3) fatty acids have shown benefit in cognitively impaired subjects, but the effect on cognitively healthy older subjects is unclear. Our aim was to determine if long-term, high-dose ω-3 ethyl esters, EPA (20:5n–3) and DHA (22:6n–3), prevent deterioration of cognitive function in cognitively healthy older adults. A total of 285 subjects with stable coronary artery disease (CAD) on statin treatment were randomly assigned to 3.36 g EPA and DHA or none (control) for 30 mo. Cognitive function was assessed in all 285 subjects at baseline and in 268 and 250 subjects who returned at 12- and 30-mo follow-up, respectively, with neuropsychological testing as a prespecified secondary outcome. A completer’s analysis, along with a sensitivity analysis carrying forward the last observation, was performed. Over the 30-mo period, subjects randomly assigned to EPA and DHA had significantly better scores than control for verbal fluency, language, and memory (mean: 1.08; 95% CI: 0.25, 1.91; P = 0.011) and 2 tests of visual-motor coordination (mean: −2.95; 95% CI: −5.33, −0.57; P = 0.015 and mean: −9.44; 95% CI: −18.60, −0.30; P = 0.043, respectively). The better scores for EPA and DHA were due to an improvement at 12 mo compared with baseline in verbal fluency, language, and memory (P = 0.047) and 2 tests of visual-motor coordination (P = 0.033 and P < 0.001, respectively), whereas control had no change. Post hoc analyses indicated no difference by age, sex, or diabetes status. Cognitively healthy older adults with stable CAD randomly assigned to high-dose EPA and DHA had improved cognitive function over a 30-mo period compared with control. These findings may be especially important for CAD patients because CAD is a risk factor for cognitive decline. This trial was registered at clinicaltrials.gov as NCT01624727.